5-year survival and safety of stereotactic ablative radiotherapy in unresectable locally advanced non-small cell lung cancer patients unfit for concurrent radio-chemotherapy:focus on patterns of local recurrence from the START-NEW-ERA non-randomized phase II trial - Arcidiacono, Fabio; Anselmo, Paola; Casale, Michelina; Zannori, Cristina; Loreti, Fabio; Enrico, Benedetta; Tassi, Valentina; Marzo, Alessandro Di; Italiani, Marco; Viani, Gustavo Arruda [UNESP]; Maranzano, Ernesto; Trippa, Fabio (Elsevier, 2025)
PURPOSE: In the early analysis of START-NEW-ERA phase 2 trial, SAbR had optimal local control and promising overall survival without ≥G3 toxicity in patients with unresectable locally advanced non-small cell lung cancer (LA-NSCLC) unfit for concurrent chemoradiation therapy (ChT-RT). We report the 5-year outcomes with a focus on patterns of local recurrence (LR). METHODS AND MATERIALS: SAbR was delivered by volumetric-modulated arc therapy to the primary tumor and regional nodes based on positron emission tomography-computed tomography. When thoracic failures occurred, we matched the SAbR planning with positron emission tomography-computed tomography images to accurately assess the LR location, precisely to determine in-field versus out-field recurrence, looking at the specific isodose line within which the LR occurred. RESULTS: Fifty patients with unresectable LA-NSCLC unfit for concurrent ChT-RT were enrolled. Median dose was 45 and 40 Gy in 5 daily fractions to tumor and regional nodes, respectively. After a median follow-up of 72 months (range, 10-108), the 3- and 5-year progression-free survival rates were 26% ± 6% and 26% ± 6%, respectively. The 3- and 5-year overall survival rates were 70% ± 6% and 46% ± 7%, respectively. No patients developed ≥G3 late toxicities. The 3- and 5-year LR-free survival rates were 64% ± 7% and 64% ± 7%, respectively. Multivariate analysis revealed squamous cell carcinoma (P = .016) and SAbR dose <40 Gy (P = .044) as significant predictors of LR. Seventeen patients experienced LR; 14/17 had squamous cell carcinoma, and 13/17 had IIIA or IIIB. Tumors that recurred were all centrally or ultracentrally located. The LR was higher in patients receiving 35 Gy compared with those receiving at least 40 Gy (P = .037). CONCLUSIONS: The 5-year outcomes of START-NEW-ERA trial confirm robust and sustained benefit in terms of safety and effectiveness of SAbR in patients with LA-NSCLC unfit for concurrent ChT-RT.